EFEKTIVITAS LAYANAN INFORMASI MELALUI MEDIA SOSIAL INSTAGRAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII DI SMP NEGERI 1 SEDAYU TAHUN AJARAN 2024/2025 - Pungguh Rezawan Rezawan; Iis Lathifah Nuryanto (Journal of Counseling and Humanistic Studies, 2025)
Excessive use of social media, especially Instagram, is one of the factors that make learning motivation low. Students often lose track of time when playing and opening social media, and many of them do not know the limits of using social media. Various problems often arise related to the lack of motivation in learning and excessive use of social media, which has a negative impact on students' academic performance and concentration. Learning motivation is the power that encourages students to learn and achieve the best achievements at school. The purpose of this study was to determine the effectiveness of information services through Instagram social media to increase the learning motivation of seventh grade students at SMP Negeri 1 Sedayu in the 2024/2025 academic year. The method used in this research is quantitative, with the type of research used is pre-experimental with One Group Pretest-Postest design. The data collection method of this study used a questionnaire questionnaire with a sample recommended by the counseling teacher totaling 22 seventh grade students of SMP Negeri 1 Sedayu. The sampling technique used is Nonprobability Sampling technique with purposive sampling type. This research data analysis technique uses paired samples test analysis. The results of the t-test analysis show the value of t = 22.454 with a p value = 0.000 0.05 which shows that information services through Instagram social media are effective in increasing student learning motivation. Based on the results of this study, it shows that the provision of information services through Instagram social media has a positive and significant effect on increasing the learning motivation of seventh grade students at SMP Negeri 1 Sedayu.